Existence of quadratic-mean almost periodic solutions to some stochastic hyperbolic differential equations - Paul H. Bezandry; Toka Diagana (Electronic Journal of Differential Equations, 2009)
In this paper we obtain the existence of quadratic-mean almost periodic solutions to some classes of partial hyperbolic stochastic differential equations. The main result of this paper generalizes in a natural fashion some recent results by authors. As an application, we consider the existence of quadratic-mean almost periodic solutions to the stochastic heat equation with divergence terms.